2021
DOI: 10.1371/journal.pone.0256650
|View full text |Cite
|
Sign up to set email alerts
|

Using an integrated knowledge translation approach to inform a pilot feasibility randomized controlled trial on peer support for individuals with traumatic brain injury: A qualitative descriptive study

Abstract: Introduction Traumatic brain injury (TBI) is estimated to affect 10 million people annually, making it a leading cause of morbidity and mortality worldwide. One cost-effective intervention that has been shown to minimize some of the negative sequelae after TBI is peer support. However, the evidence supporting the benefits of peer support for individuals with TBI is sparse and of low quality. Integrated knowledge translation (iKT) may be one approach to optimizing the evaluation of peer support programs among i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…This suggests that motivational problems rooted in psychological mechanisms may be attenuated through peer-assisted activities. Similar outcomes about the ways in which community-based peer-support programs can have a positive impact on recovery after TBI through acceptance and encouragement have been identified (30). Our findings extend those results with the positive influence that peers can have on motivation to participate in health-related PA behaviors in the community after moderate-to-severe TBI.…”
Section: Discussionsupporting
confidence: 85%
“…This suggests that motivational problems rooted in psychological mechanisms may be attenuated through peer-assisted activities. Similar outcomes about the ways in which community-based peer-support programs can have a positive impact on recovery after TBI through acceptance and encouragement have been identified (30). Our findings extend those results with the positive influence that peers can have on motivation to participate in health-related PA behaviors in the community after moderate-to-severe TBI.…”
Section: Discussionsupporting
confidence: 85%
“…Our feasibility study identified that peer support was acceptable to mentors and mentees, with numerous perceived benefits, indicating a high potential for effectiveness and likelihood of improving outcomes. These findings are consistent with those more recently reported by Lau et al , 21 whose qualitative descriptive study was also performed to support a randomised controlled trial on peer support after brain injury.…”
Section: Introductionsupporting
confidence: 92%
“…Specifically, they can enact antistigma initiatives for TBI that include narratives of TBI survivors experiences, “myth busting” information, and a discussion of the impact of stigma on prejudiced labeling and behaviors (Szeto & Dobson, 2010; Tsatsou, 2021; Werner & Scior, 2016). Sytems should consider implementing peer support or mentoring programs to reduce both isolation and stigma (Lau et al, 2021), as well as increase the presence of in-person and remote support groups, group-based interventions, and group-based community reintegration activities (e.g., walking group) (Chouliara & Lincoln, 2016; Neumann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%